EXPLORING WILLINGNESS TO COMMUNICATE IN EFL CLASSROOM: A CASE IN INDONESIAN SECONDARY EDUCATION - Siti farida; Dyah Ayu Nugraheni (PT. Hasba Edukasi Mandiri, 2025)
Currently, English communication is an important concern in the educational environment. In fact, many students feel uncomfortable or lack confidence when speaking English with teachers and other students. In one of the secondary schools in Sukojember, this study attempts to identify the factors that influence students' willingness to communicate in class and the strategies used by teachers to increase students' willingness to speak in class. This study uses qualitatve methods and uses narative design.The reserhers uses semi structured interview face to face.The resarchers uses thematic analysis to analyze the data.In study,the researchers use theory maclyntyre and the theory of vosngila 2016 to answer the researcher’s qustions.Resarcher use member checking tecnique from lincoln and guba 1985 as data trust. Based on the results of the interview,there are five factors that influence students willingness to communicate,these factors are 1.learning anxiety,2.sudent motivation,3.Class atmosphere,4.teacher role and 5.interluctor.And several teacher stratgies to increase students willingness to communicate these strategies are 1. Remembering to give positive feedback 2.learning methods 3.simple assigments.